Research Progress on Micro Inflammatory Status of Chronic Kidney Disease - Luo, Nana; Fan, Ping (Journal of Contemporary Medical Practice, 2025)
The occurrence of microinflammation is affected by various factors, and its mechanism is relatively complex. Moreover, this state can have adverse effects on patients with chronic kidney disease (CKD). Currently, for the microinflammatory state existing in CKD patients, Western medicine mainly intervenes through methods such as drug therapy, exercise therapy, and optimized dialysis. In terms of traditional Chinese medicine’s role in improving the microinflammatory state in the bodies of CKD patients, Reflecting the unique advantages possessed by traditional Chinese medicine.